Some Empirical Estimates of the Risk Structure of Interest Rates - SARIG, ODED; WARGA, ARTHUR (Journal of Finance, 1989)
ABSTRACT This paper investigates the risk structure of interest rates using pure discount bonds. The most striking feature of our estimates of default‐risk premia is the resemblance of their time profile to the theoretical time profile obtained by Merton (1974) .